2016
DOI: 10.1159/000441377
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjuvant Chemotherapy and Prognostic Factors for Patients with Extrahepatic Bile Duct Cancer

Abstract: Background: Surgical resection is the only curative treatment for extrahepatic bile duct cancer. Additionally, the recurrence rate after curative surgery is relatively high, requiring adjuvant therapy. However, the efficacy of adjuvant chemotherapy compared with surgery alone has not yet been clarified. This study aimed to evaluate the efficacy of adjuvant chemotherapy and identify prognostic factors influencing survival in extrahepatic bile duct cancer patients who underwent curative surgical resection. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In another recent study with biliary tract cancer patients undergoing resection with curative intent, the worse 3-year OS was observed among patients with an abnormally high (≥37 U/ml) preoperative as well as postoperative CA19-9 levels by comparison with those with either the high preoperative and normal postoperative CA19-9 levels, or normal preoperative CA19-9 level (3-year OS rate 31, 73, and 70.4% respectively, p<0.001) (18). The postoperative CA19-9 level (<37 vs. ≥37 U/ml) was an independent prognostic factor for a long-term survival (HR=7.296, p=0.002) in the study with 97 patients with the extrahepatic bile duct cancers as well (19).…”
Section: Discussionmentioning
confidence: 72%
“…In another recent study with biliary tract cancer patients undergoing resection with curative intent, the worse 3-year OS was observed among patients with an abnormally high (≥37 U/ml) preoperative as well as postoperative CA19-9 levels by comparison with those with either the high preoperative and normal postoperative CA19-9 levels, or normal preoperative CA19-9 level (3-year OS rate 31, 73, and 70.4% respectively, p<0.001) (18). The postoperative CA19-9 level (<37 vs. ≥37 U/ml) was an independent prognostic factor for a long-term survival (HR=7.296, p=0.002) in the study with 97 patients with the extrahepatic bile duct cancers as well (19).…”
Section: Discussionmentioning
confidence: 72%
“…Some retrospective reports suggest that adjuvant chemotherapy is indicated regardless lymph node involvement in distal bile duct cancer [25][26][27] and in periampullary cancer [23]. However, Lee et al reported that postoperative adjuvant chemotherapy did not improve survival after surgical resection for extrahepatic bile duct cancer [28]. There were no differences in relapse-free survival and overall survival between patients who underwent adjuvant chemotherapy and those who went without adjuvant chemotherapy (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Bile duct cancer (BDC) is a relatively rare malignancy with a poor prognosis that develops from the intra-or extra-hepatic bile ducts. Surgical resection is the only curative treatment for BDC; however, recurrence after resection is common, and more than two-thirds of lesions are unresectable (4). Treatment with the nucleotide analogue gemcitabine, alone or in combination with cisplatin, is considered the standard first-line chemotherapy in advanced BDC (5).…”
mentioning
confidence: 99%